Exploring Teachers’ Independent Efforts in Enhancing Professional Competence at Madrasah - Suaib, Suaib; Nasir, Nasir; Muallimah, Muallimah (Magister Administrasi Pendidikan, Universitas Muhammadiyah Kendari, 2025)
This study aims to identify and analyze the independent efforts undertaken by teachers at Madrasah Aliyah Al-Islam Meeto in improving their professional skills. It also explores the supporting and inhibiting factors in these efforts, as well as their impact on the quality of learning. Using qualitative methods through teacher interviews and document analysis, the findings reveal that teachers’ motivations vary, ranging from moral responsibility to the demands of scientific development. Independent efforts identified include reading academic literature, participating in training, and engaging in collegial collaboration. Nevertheless, teachers face obstacles such as limited time and restricted access to appropriate learning resources. Despite these challenges, the independent efforts contribute positively to enhancing the quality of learning and improving students’ understanding.